answersLogoWhite

0


Best Answer

You cannot solve it since only one side of an equation is given. If the equation was y4 + 5y2 - 84 = 0 then y4 + 12y2 - 7y2 - 84 = 0 or y2*(y2 + 12) - 7*(y2 + 12) = 0 or (y2 - 7)*(y2 + 12) = 0 then y2 = 7 or y2 = - 12 y = +or- sqrt(7) and, if you are in the complex domain, also y = +or- i*sqrt(12) where i is the imaginary square root of -1.

User Avatar

Wiki User

โˆ™ 2009-09-03 10:47:08
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.72
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
335 Reviews

Add your answer:

Earn +20 pts
Q: How do you solve y4-84 plus 5y2?
Write your answer...
Submit
Related questions

What is the recoprocal of 5y2 plus 9y?

1/5y2+9


Factor 5y2-22y plus 8?

That is the most simplifiable version of this equation.


Simplify the expression 4x2-8y plus 3x-9x2 plus 10y?

-5y2+3x+2y


4x-5y2 12x8 plus 15y solve by elimination?

Without any equality signs the given terms can't be considered as simultaneous equations and so therefore no solutions are possible.


(-3y2 and minus 8) and minus (-5y2 plus 1)?

it's MINUS 182.5


How do you solve 3.5y2 plus 2.6y-8.2 equals 4y2-6.9y using the quadratic formula?

Multiply each item by 10 to give whole numbers then move items to give ay2+by+c=0 3.5y2+2.6y-8.2=4y2-6.9y multiply by 10 35y2 + 26y - 82 = 40y2 -69y subtract 35y2 from both sides 26y - 82=5y2 -69y subtract 26y from both sides -82 = 5y2 - 95y add 82 to each side 0 = 5y2 - 95y +82 or 5y2 - 95y +82 = 0


X equals 5y2-20y plus 15?

x isn't in the calculation so it cant be solved.


Factor the trinomial 9x2 - 18xy plus 5y2 and Factor the trinomial 4x2 plus 24x plus 11?

(3x - y)(3x - 5y) and (2x + 1)(2x + 11)


What is 15y2 plus 45y - 9 equals 4y - 5y2?

15y2 + 45y - 9 = 4y - 5y2; thus, 20y2 + 41y - 9 = (5y - 1)(4y + 9) = 0. Therefore, the solution to the equation given is, y = 1/5 or -2¼.


What is the greatest common factor of 20y3 5y2 45y?

The GCF is 5y.20y3 = (5y)(4y2)5y2 = (5y)(y)45y = (5y)(9)


How do you solve 4y plus x equals 8?

How do you solve 4y plus x equals 8


How do you factor out x squared plus 8xy plus 15y squared?

x2 + 8xy + 15y2 = (x + 3y) (x + 5y)


B equals 10 plus a solve for a?

Not enough information to solve


How do you factor 80x2 5y2?

5(16x^2 + y^2)


What is the factor of 5y2-19y-4?

(5y+1)(y-4)


What is 10y squared minus 15y squared?

10y2 - 15y2 = -5y2


5y2 - 2y - 3 Factor completely?

(5y + 3)(y - 1)


Is x 5y2 - 2 a function?

x5y2 - 2 = 0 ... makes sense


How to solve x plus y for graphing?

You cannot solve x plus y since that is an expression, not an equation (nor inequality).


How do you solve a equals b plus c plus d solve for c?

If: a = b+c+d Then: c = a-b-d


How do you solve -2 plus 5?

+3


Solve -2 plus 5?

3?


Solve this 23 plus 45 what is the answer?

68


How do you solve 3.914 plus 8.73?

12.644


How do you solve 5x plus 30?

There's nothing to solve, it's simply an expression.